2023
DOI: 10.1111/jzo.13092
|View full text |Cite
|
Sign up to set email alerts
|

Body size predicts prey preference but not diet breadth in pythons

Abstract: For gape‐limited predators like snakes that swallow their prey whole, large‐bodied species with wide gapes should theoretically be able to consume a more diverse range of prey than smaller species with narrow gapes and, therefore, may have broader diets. However, in cases where large‐bodied species exclude small prey, their diets may not necessarily be more taxonomically diverse compared to smaller species. Thus, while body size can potentially predict broad dietary preferences, it cannot always predict diet b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 55 publications
0
1
0
Order By: Relevance
“…For snakes, the size of their mouth opening establishes the upper limits for the maximum size of ingestible prey and, therefore, directly influences which prey they can or cannot consume (Arnold, 1993; Cundall & Greene, 2000). Furthermore, the size of the snake can predict the dietary preferences of certain species, with smaller snakes exhibiting a preference for smaller ectothermic prey (Barends & Naik, 2023). Our study revealed a significant correlation between prey size and feeding preference, relying solely on the scent of the prey as a cue.…”
Section: Discussionmentioning
confidence: 99%
“…For snakes, the size of their mouth opening establishes the upper limits for the maximum size of ingestible prey and, therefore, directly influences which prey they can or cannot consume (Arnold, 1993; Cundall & Greene, 2000). Furthermore, the size of the snake can predict the dietary preferences of certain species, with smaller snakes exhibiting a preference for smaller ectothermic prey (Barends & Naik, 2023). Our study revealed a significant correlation between prey size and feeding preference, relying solely on the scent of the prey as a cue.…”
Section: Discussionmentioning
confidence: 99%